Impact of Communication and Information Technology on Finance and Human Capital in Government Systems - Eddy Priyanto; Ema Sulisnaningrum; Murniati Murniati (AIBPM Publisher, 2023)
The purpose of this study is to investigate the concept in previous research regarding human capital through Impact of Communication and Information (ICT). We use Content Analysis to compile scholarly articles from emerald and Korean science as well as books written by experts in ICT and Financial Information. The government system has an impact on government regulations and policies, related to the financial system, the government system affects operational processes and the development of financial technology. Not only that, but the government system also determines the education system which has an impact on the development of the quality of human resources. Technology and information play a very critical role both in economic growth, financing, and human needs, so that they become very important in human life, including in finance and human resource development. The ability of information and communication technology (ICT) today and in the future is very much needed by the community to be productive in today's world of work. The application of technology to e-finance and the emergence of e-finance can be applied to the banking and financial services business. Information and technology communication engages the active online social of rural and urban families, which encourages them to participate in digital finance. In addition, the importance of social connections in the online world is an alternative way to complement the role of offline social interactions in terms of increasing digital financial engagementÂ Keywords: Information Communication Technology, Finance, Government, Human capital